Cohesion Analysis of L2 Writing: The Case of Iranian Undergraduate EFL Learners - Sadighi, Firooz; Heydari, Pooneh (Mediterranean Journal of Social Sciences, 2012)
This study aimed at investigating the most frequent cohesive errors committed by Iranian undergraduate EFL learnersat different levels of proficiency as well as the sources of cohesive errors. An overall number of 67 undergraduate students atShiraz Azad University participated in this study. To have three groups of learners with different proficiency levels, OxfordPlacement Test 1B1 (Allan, 1985) was administered. To achieve the objectives of the study, the participants were given a writingtask requiring them to write an approximately 200-word narrative composition. Then, the compositions were scored based on thetaxonomy developed by Halliday and Hasan (1976). Finally, the data were analyzed through appropriate procedures usingquantitative methods. Regarding the frequencies and percentages of errors it was found that low-level learners' most frequenterrors were involved in references (20), followed by errors in lexical (14), and conjunctive cohesion (1). Besides, the findingsshowed that errors in references were the most common (17), followed by errors in lexical (13), and conjunction cohesion (2) inthe mid-level learners' narrative compositions and, finally, the high-level learners' most frequent errors were involved in lexicalcohesion (17), references (14), conjunction cohesion (3), and substitution (1).This study also allowed for an examination of thesources of cohesive errors. It was found that errors in the use of relative pronouns, conjunctions, along with different forms ofrepetition appeared because of the incomplete knowledge of the learners—intra-lingual causes. Furthermore, in this study, theerrors in the use of personal-, possessive-pronouns, demonstratives and collocations were among the inter-lingual causes oferrors.